TINJAUAN HUKUM ISLAM TERHADAP UPAYA KANTOR URUSAN AGAMA KECAMATAN DUAMPANUA KABUPATEN PINRANG DALAM MEWUJUDKAN KELUARGA SAKINAH - Firman; Muh. Saleh Ridwan; Hartini Tahir (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2023)
This research discusses the review of Islamic law regarding the efforts of the religious affairs office of Duampanua District, Pinrang Regency, in creating a sakinah family. The purpose of this research is to determine the implementation of family counseling at the Religious Affairs Office, Duampanua District, Pinrang Regency, and to determine the review of Islamic law regarding the realization of a sakinah family. This research uses a qualitative method with normative theology. The data collection method used is observation, interviews, and questionnaires. Data processing and analysis techniques were carried out through data reduction, data display, and conclusion drawing and verification. The results of this study indicate that the type of counseling that is carried out is face-to-face, dialogue, and through discussion. The people of Duampanua District who are not married receive guidance every Monday and Thursday, while the people of Duampanua District who are married receive guidance that is programmed every quarter or every 3 months. Overall, the KUA's efforts are in line with one of the goals of marriage in the Quran, namely creating a sakinah, mawaddah, and warahmah family (QS. Ar-Rum: 21).